Densidade e flutuação populacional de ácaros fitófagos em cultivares de soja - Arnemann, Jonas André (2013)
ARTIGO 1: The spider mites occurrence and population density were studied at two times in reproductive growth stage in 22 soybean cultivars in Rio Grande do Sul, Brazil. The main specie found in this study was Mononychellus planki. The cultivars Nidera 5909 RG, M-soy 8000 RR, Nidera NS 4823 RR, FTS IPÊ RR and FEPAGRO 36 were not favorable to the development of spider mites because they show the lowest population densities. The cultivars Nidera A 4725 RG, SYN 9070 RR, SYN 1059 RR, SYN 3358 RR and BMX Magna RR were more favorable, showing the highest population densities of this pest. ARTIGO 2: The spider mites population fluctuation of was studied in two trials, located at (1) SãoSepé and (2) Santa Maria, in Rio Grande do Sul State, Brazil. We evaluated 20 soybean cultivars in São Sepé and 25 in Santa Maria, where we made 10 and 11 samples of leaves with spider mites, respectively, over the development cycle of soybean plants. There was interaction between cultivars and dates of sample, evaluated at both sites, indicating that population varies for each cultivar unevenly over time. Equations modeling the population dynamics of spider mites were estimated for each cultivar, with cubic adjustments equations for most cultivars. Analysis of all data from both locations indicated cultivars FUNDACEP 57 RR, RR NK 7059 (V-max RR), SYN 1059 RR (V-top RR) and SYN 1161 RR were with lower spider mites densities, and cultivars NS 5858 RR, RR Energy BMX, Roos Camino RR, RR TURBO BMX and Uranu RR FPS with the highest density of spider mites.